Percutaneous Nephrolithotomy (PCNL) in Older and Younger Patients at a Tertiary Hospital in Surabaya, Indonesia - Ali, Muhammad Wahyu; Azmi, Yufi Aulia; , Tarmono; Soebadi, Doddy M. (Folia Medica Indonesiana, 2023)
Highlights: • Percutaneous nephrolithotomy (PCNL) in older patients is as effective and safe as in younger patients. • It is a viable option for managing renal stones in older patients with indications, although blood transfusions are frequently required. Abstract: Percutaneous nephrolithotomy (PCNL) for renal and proximal ureteral stone treatment among the elder population is considered challenging due to the complication risk associated with comorbidity and lower functional reserve. Patients older and younger than 60 years old were compared for efficacy and safety in following PCNL procedures. Consecutive patients who underwent PCNL from 2019-2021 in a single center were divided into patients aged at least 60 years (group I) and patients aged under 60 years (group II). Single stage fluoroscopic-guided PCNL were used for the entire study population. Patients' habitus, stone-related, and operative characteristics were compared. The two groups' PCNL success and complication rates were evaluated. A total of 245 patients, comprising 65 in group I and 180 in group II, were included for analysis. Diabetes mellitus prevalence was higher in group I (30.8% vs 18.9%). However, the study population did not show a significant difference in regard to comorbidity. Operative time, success rate (80% vs 74.4%), and complication rate (16.9% vs 15.6%) did not statistically differ (p>0.05). Transfusion rate was higher among patients aged at least 60 years (p=0.018). Based on the multivariate analysis, stones located in the renal pelvis was the factor which contributed to the success rate. In conclusion, percutaneous nephrolithotomy is a safe and effective procedure for treating renal and proximal ureteral stones in the older population. Blood transfusions are more frequently given, in part, due to bleeding risk among older patients.